Glutamate triggers intracellular Ca2+ oscillations and nitric oxide release by inducing NAADP‐ and InsP3‐dependent Ca2+ release in mouse brain endothelial cells. Issue 4 (19th November 2018) - Zuccolo, Estella; Kheder, Dlzar A.; Lim, Dmitry; Perna, Angelica; Nezza, Francesca Di; Botta, Laura; Scarpellino, Giorgia; Negri, Sharon; Martinotti, Simona; Soda, Teresa; Forcaia, Greta; Riboni, Laura; et al.
Abstract : The neurotransmitter glutamate increases cerebral blood flow by activating postsynaptic neurons and presynaptic glial cells within the neurovascular unit. Glutamate does so by causing an increase in intracellular Ca 2+ concentration ([Ca 2+ ]i ) in the target cells, which activates the Ca 2+ /Calmodulin‐dependent nitric oxide (NO) synthase to release NO. It is unclear whether brain endothelial cells also sense glutamate through an elevation in [Ca 2+ ]i and NO production. The current study assessed whether and how glutamate drives Ca 2+ ‐dependent NO release in bEND5 cells, an established model of brain endothelial cells. We found that glutamate induced a dose‐dependent oscillatory increase in [Ca 2+ ]i, which was maximally activated at 200 μM and inhibited by α‐methyl‐4‐carboxyphenylglycine, a selective blocker of Group 1 metabotropic glutamate receptors. Glutamate‐induced intracellular Ca 2+ oscillations were triggered by rhythmic endogenous Ca 2+ mobilization and maintained over time by extracellular Ca 2+ entry. Pharmacological manipulation revealed that glutamate‐induced endogenous Ca 2+ release was mediated by InsP3 ‐sensitive receptors and nicotinic acid adenine dinucleotide phosphate (NAADP) gated two‐pore channel 1. Constitutive store‐operated Ca 2+ entry mediated Ca 2+ entry during ongoing Ca 2+ oscillations. Finally, glutamate evoked a robust, although delayed increase in NO levels, which was blocked by pharmacologically inhibition of the accompanying intracellular Ca 2+ signals. Of note, glutamate induced Ca 2+ ‐dependent NO release also in hCMEC/D3 cells, an established model of human brain microvascular endothelial cells. This investigation demonstrates for the first time that metabotropic glutamate‐induced intracellular Ca 2+ oscillations and NO release have the potential to impact on neurovascular coupling in the brain. Abstract : Glutamate induces intracellular Ca 2+ oscillations in mouse brain microvascular endothelial cells. Glutamate‐induced intracellular Ca 2+ oscillations lead to robust, although delayed, nitric oxide release. Brain microvascular endothelial cells could play a crucial role in neurovascular coupling during synaptic activity.